Polyaniline based metal-organic framework composites for hydrogen fuel cells - Ramohlola, Kabelo Edmond (My University, 2017)
In order to meet the great demand of energy supply globally, there must be a transition from dependency on fossil fuel as a primary energy source to renewable source. This can be attained by use of hydrogen gas as an energy carrier. In the context of hydrogen fuel cell economy, an effective hydrogen generation is of crucial significant. Hydrogen gas can be produced from different methods such as steam reforming of fossil fuels which emit greenhouse gases during production and from readily available and renewable resources in the process of water electrolysis. Hydrogen generated from water splitting using solar energy (photocatalysis) or electric energy (electrocatalysis) has attracted most researchers recently due to clean hydrogen (without emission of greenhouse gases) attained during hydrogen production. In comparison with photocatalytic water splitting directly using solar energy, which is ideal but the relevant technologies are not yet commercialized, electrolysis of water using catalyst is more practical at the current stage. The platinum group noble metals (PGMs) are the most effecting electrocatalysts for hydrogen evolution reactions (HER) but their scarcity and high cost limit their application. In this study, we presented the noble metal free organic-inorganic hybrid composites and their HER electrocatalysis performances were investigated. Polyaniline-metal organic framework (PANI/MOF) composite was prepared by chemical oxidation of aniline monomer in the presence of MOF content for hydrogen production. The properties of PANI, MOF and PANI/MOF composite were characterised for their structure and properties by X-ray diffraction (XRD), field-emission scanning electron microscopy (SEM), Fourier transform infrared (FTIR), thermogravimetric analysis (TGA), Raman, transmission electron microscopy (TEM), ultraviolet-visible spectroscopy (UV-vis), atomic absorption spectroscopy (AAS), square wave (SWV) and cyclic voltammetry (CV). There was a clear interaction of MOF on the backbone of the PANI matrix through electrostatic interaction as investigated by both Raman and FTIR. The MOF exhibited irregular crystals with further wrapping of MOF by PANI matrix as evidenced by both SEM and TEM analyses. The PANI composite exhibited some nanorods and microporous structure. x The determined energy band gap of the composite was in good agreement with previously reported catalysts for hydrogen evolution reaction (HER). The thermal stability of PANI increased upon addition of MOF. Experiments probing the electrochemical, HER and photophysical properties revealed that the composite was very stable and robust with significant improvement in properties. The resulting composite is a promising low-cost and environmentally friendly hydrogen production material. In this work we also reported about novel poly (3-aminobenzoic acid)-metal organic framework referred as PABA/MOF composite. Spectroscopic characterisations (UV-vis and FTIR) with support of XRD and TGA revealed a successful interaction between PABA and MOF. Morphological characterisation established that PABA is wrapping MOF and the amorphous nature of the materials were not affected. The catalytic effect of PABA and PABA/MOF composites on HER was studied using exchange current density and charge transfer coefficient determined by the Tafel slope method. A drastic increase in catalytic H2 evolution was observed in PABA and composite. Moreover, they merely require overpotentials as low as ~-0.405 V to attain current densities of ~0.8 and 1.5 Am-2 and show good longterm stability. We further demonstrated in the work the electrocatalytic hydrogen evolution reaction of MOF decorated with PABA. These novel MOF/PABA composites with different PABA loading were synthesised via in situ solvothermal synthesis of MOF in the presence of PABA. It was deduced that PABA with different loading amount have an influence on the morphologies, optical properties and thermal stabilities of MOF. Interestingly, the MOF/PABA composites exhibited the great significant on the HER performance and this is potentially useful in HER application for hydrogen fuel cell.
Thesis (M. Sc. (Chemistry)) -- University of Limpopo, 2017.
Keywords: Hydrogen fuel cells; Fossil fuel; Hydrogen as fuel; Fuel cells